Negotiating difference in French Louisiana music : categories, stereotypes, and identifications. - Le Menestrel, Sara (University Press of Mississippi, 2015)
This book explores the role of music in negotiating difference. It brings to light processes of differentiation and social stereotypes and hierarchies at at work in the evolving French Louisiana musical field. It also draws attention to the interactions between binary oppositions such as black and white, urban and rural, differentiation and creolization, traditional and modern, and local, national and global. The book argues for the importance of desegregating the understanding of French Louisiana music by situating it beyond ethnic or racial identifications, bringing to light the importance of regional identification. The musical genealogy and categories in use are legitimized through an omnipresent racial imaginary that frames African and European lineage as a foundational difference. Instead of seeing the discourses of origins and mixing as contradictory, the field and the way music is practiced show that they continually interact. French Louisiana musicians navigate between multiple identifications, music styles and legacies while market forces, outsider’s interest and geographical mobility also contribute to shape their career strategies and musical choices. This work also demonstrates the decisive role of non-natives’ interest and mobility in the validation, evolution, and reconfiguration of French Louisiana music. Finally, the distinctiveness of South Louisiana with respect to the rest of the country appears both nurtured and endured, revealing the intricacies of political domination and regionalism -- Présentation de l'éditeur.